Type A botulinum toxin in combined rehabilitation of infantile cerebral paralysis children and teenagers - Ye. A. Kislyakova; N. N. Maslova; I. L. Alimova (Бюллетень сибирской медицины)
Seventy six patients with infantile cerebral paralysis in the form of spastic diplegia were studied in dynamics. The patients were divided into groups according to their age (3–6; 7–14; and 15–18 years) and severity of motor disorders. It has been shown that combined rehabilitation (massage, physiotherapy, remedial gymnastics, Gravistat or Adel medical suits, acupuncture or laser acupuncture) along with use of BTA preparations improves physical and motor development of patients due to muscle tone reduction, increase of motions in joints, and improvement of motor skills, especially, if treatment is started in early ages (before 6 years) at moderate severity of the disease and additional use of BTA in m. pectoralis major.